2021
DOI: 10.1039/d1dt00060h
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel GnRH and Tat48–60 based luminescent probes with enhanced cellular uptake and bioimaging profile

Abstract: There is a clear need to develop photostable chromophores for bioimaging with respect to the classically utilized green fluorescent dye fluorescein. Along these lines, we utilized a phosphorescent carboxy-substituted ruthenium(II)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…A 3-dimensional view of HCT116 cells shows that the 1NPs ⊂ PF-127 are present within the cytoplasm near the DAPI-stained blue nuclear area (Figure c,d). Organic chromophores have been reported to be quite photostable, and after their efficient cellular uptake, they can be used for their targeted cellular bioimaging profiles. , Our cellular internalization results also suggested that these organic push–pull chromophores possess strong capabilities to be applied in biomedical sciences in the field of bioimaging. After the qualitative assessment of cellular uptake of nanoparticles using confocal microscopy, flow cytometry analysis was carried out for quantitative assessment of cellular internalization of nanoparticles inside metabolically active HCT116 colorectal cancer cells.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…A 3-dimensional view of HCT116 cells shows that the 1NPs ⊂ PF-127 are present within the cytoplasm near the DAPI-stained blue nuclear area (Figure c,d). Organic chromophores have been reported to be quite photostable, and after their efficient cellular uptake, they can be used for their targeted cellular bioimaging profiles. , Our cellular internalization results also suggested that these organic push–pull chromophores possess strong capabilities to be applied in biomedical sciences in the field of bioimaging. After the qualitative assessment of cellular uptake of nanoparticles using confocal microscopy, flow cytometry analysis was carried out for quantitative assessment of cellular internalization of nanoparticles inside metabolically active HCT116 colorectal cancer cells.…”
Section: Resultsmentioning
confidence: 52%
“…Organic chromophores have been reported to be quite photostable, and after their efficient cellular uptake, they can be used for their targeted cellular bioimaging profiles. 52,53 Our cellular internalization results also suggested that these organic push−pull chromophores possess strong capabilities to be applied in biomedical sciences in the field of bioimaging. After the qualitative assessment of cellular uptake of nanoparticles PDT of Colorectal Cancer Cells.…”
Section: In Vivo Biodistribution Study Using An In Vivo Imaging Syste...mentioning
confidence: 99%
“…Similar to PROTACs and other prodrugs, the effect of the linker is highly influential toward the overall bioactivity profile of the final HATP and should be selected in a prudent manner [ 16 , 33 , 34 ]. Additional decorations: The utilization of additional modalities like tumor-homing elements (e.g., peptides [ 35 , 36 , 37 ], D-biotin [ 6 , 38 ]) or nano-formulations [ 39 ] can help ameliorate particular challenges. They are typically invoked to enhance tumor specificity by offering more precise delivery and the overall potency of the developed HATP.…”
Section: Introductionmentioning
confidence: 99%
“…Additional decorations: The utilization of additional modalities like tumor-homing elements (e.g., peptides [ 35 , 36 , 37 ], D-biotin [ 6 , 38 ]) or nano-formulations [ 39 ] can help ameliorate particular challenges. They are typically invoked to enhance tumor specificity by offering more precise delivery and the overall potency of the developed HATP.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of new analytical techniques has led to a better understanding of the mechanistic basis of tumor adaptation and has facilitated the development of new conjugates that selectively target tumors, diminishing the uncontrolled toxicity [8]. Specifically, such conjugates usually consist of molecules that are selectively recognized by specific receptors that are uniquely expressed or overexpressed on the surface of malignant tumor cells and lead to the internalization of the entire conjugate (e.g., peptides [9]). Thus, the drug can be released or activated primarily by the tumor microenvironment and selectively act cytotoxically within the tumor area [10].…”
Section: Introductionmentioning
confidence: 99%